Dietary factors and associated health effects among patients with vitamin D deficiency - Maisha Mehjabin; Momena Shirin; M. Abiduzzaman (International Journal Of Community Medicine And Public Health, 2026)
Background: Vitamin D deficiency is prevalent among men and women alike and is often left untreated in developing countries. Vitamin D deficiency and its associated health problems can be controlled if dietary intake is properly maintained. The study objective was to understand the dietary habits and the problems faced by patients of a hospital in Dhaka due to vitamin D deficiency. Methods: Total 133 patients were selected through convenience sampling, and their vitamin D levels were collected from the medical records. Other data were collected from a previously set questionnaire. Results: Total 56 (42.1%) were men, and 77 (57.9%) were women among the patients. 42 (31.6%) of the vitamin D-deficient people were obese in this study. 17 (12.8%) people still had severe (level